The importance of early diagnosis in Jacobsen Syndrome: A systematic literature review (Research, Society and Development, 2024)
Jacobsen syndrome is a contiguous genetic syndrome based on the terminal deletion of the long arm of chromosome 11, which was first defined by Jacobsen in 1973. It is characterized as a clinical disorder caused by segmental aneusomy and monosomy due to deletion of the terminal region 11q23, in which the deletion in 11q varies between 7 and 20 Mb, and deletions smaller than 2.9 Mb are associated with this syndrome, and it is suggested that gene deletion has a cumulative effect on the prognosis of the disease. This syndrome is considered rare, as it has a low incidence in the general population of approximately 1 in 100,000 births. The diagnosis of Jacobsen syndrome includes physical examination and clinical history, based on psychomotor regression, facial dysmorphism and the appearance of thrombocytopenia. Therefore, it is crucial that an early diagnosis is made, as this can interfere with the worsening and effects that Jacobsen Syndrome brings to the patient. That said, the general objective of this article is to identify the clinical signs for early detection of Jacobsen Syndrome through a systematic literature review. The research was carried out with 09 articles, identifying a lack of research in the area, corroborating the researchers' hypothesis. As it is a rare disease, there are still few studies on it and, consequently, few professionals have knowledge about the syndrome, making early diagnosis and treatment even more difficult.